Development of a Web-Based Postage Revenue Information System for Postal Packages in Pulau Temiang: Pengembangan Sistem Informasi Pendapatan Ongkir Paket Pos Pulau Temiang Berbasis Web - Effri Saputra; Zainul Aras Z; Gunawan Ali; Raimon Efendi (International Journal of Technology Vocational Education and Training, 2021)
This research discusses the design of a postage revenue information system for Temiang Island Post packages using the waterfall method. This method was chosen to ensure a structured and organized development process. The stage involves analyzing system requirements through interviews with stakeholders and in-depth understanding of business processes. System design includes database structure, user interface, and business logic, followed by the implementation phase utilizing web-based technology. Testing is carried out thoroughly to ensure system reliability, security and performance. This includes functionality, security, and performance testing to ensure that the system can operate effectively in a production environment. The system maintenance stage is implemented to ensure the system remains optimal and can adapt to changing needs. The results of this research are expected to provide practical guidance for organizations such as Pos Pulau Temiang in designing a web-based postage revenue information system. By applying the waterfall method, it is hoped that system development can be carried out in a structured and efficient manner. The conclusion of this research is that the waterfall method can be an effective approach in designing a web-based information system for postage revenue management in the Temiang Island Post operational environment.